The impact of social commerce on the purchase intentions of Millennials using Facebook - Krishna K. Govender; Ramnarain Yavisha (Innovative Marketing)
This study examined the impact of social commerce on the purchase intentions of Millennials who use Facebook by exploring how social commerce constructs influence consumer trust. A quantitative research approach was used and data were collected via an ‘online’ survey. The target population was 386 young adults aged 25 to 34 residing in KwaZulu-Natal, South Africa, referred to as Millennials, and comprises the largest group of users on Facebook. Convenience sampling, namely snowball sampling, was used to target participants. It was found that social commerce constructs significantly influence trust, which positively influences consumer purchasing decisions. The results of the study showed that trust explained 68% of the variance in purchasing intentions. Since trust is an integral and vital component of social commerce, the role of social commerce constructs and social support is to build trust in the ‘online’ context and consumers’ intention to buy. This suggests that businesses should monitor the quality and content of the engagements around their brands on social media, as information sharing in social commerce has a significant impact on consumer decisions, i.e., purchase intentions.